(x)(x+1)=10x

Simple and best practice solution for (x)(x+1)=10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x)(x+1)=10x equation:


Simplifying
(x)(x + 1) = 10x

Reorder the terms:
x(1 + x) = 10x
(1 * x + x * x) = 10x
(1x + x2) = 10x

Solving
1x + x2 = 10x

Solving for variable 'x'.

Reorder the terms:
1x + -10x + x2 = 10x + -10x

Combine like terms: 1x + -10x = -9x
-9x + x2 = 10x + -10x

Combine like terms: 10x + -10x = 0
-9x + x2 = 0

Factor out the Greatest Common Factor (GCF), 'x'.
x(-9 + x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-9 + x)' equal to zero and attempt to solve: Simplifying -9 + x = 0 Solving -9 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + x = 0 + 9 x = 0 + 9 Combine like terms: 0 + 9 = 9 x = 9 Simplifying x = 9

Solution

x = {0, 9}

See similar equations:

| 7+9=11(z-8) | | 2x^2+17x-55=0 | | -16t^2+96t+80=124 | | 2/7m-1/3=4/5 | | 20+20+z=-20+5z | | -2y+16=4x | | -16t^2+96t+80=125 | | 28=3(2p-6) | | 7h(11h-8)= | | 3x(2x+20)=180 | | Y=4(-3x-3) | | 18x^6*(12x^2-24x)=0 | | Y=10x-4-6x+12 | | -2t+8=-t | | 18x^6*12x^2-24x=0 | | Y=5(3x-2) | | Y=8x+7+5x+3 | | 5x+4(2x+3)=x | | -10-2r=10+8r+10 | | (X^2+26x-39)=0 | | 5-7/2x | | A+B=74 | | 46+9x=146-3x | | 18-6n=3(2-n) | | f(x)=x-x-12 | | 3y-6=36 | | lnx+lnx^6=14 | | Y=-6/5x-3/5 | | 12x+10y=-6 | | (9/2)(-33/10) | | -2-2m=-9-m | | 10(1a+3b)=-20 |

Equations solver categories